Islamic guiding principles for sustainable development: a case study of International Islamic school (IIS),IIUM - Amanullah, Muhammad (International Islamic University Malaysia, 2016)
Sustainable development is a term that signifies development for the well-being of both present and future generations of humans. It has become universal concern of all the modern nations. Yet, a set of comprehensive conditions or guiding principles for sustainable development is yet to be devised. Islam has guiding principles of sustainable development. By analysing the related Qur’anic verses and Prophetic ahadith, this paper intends to develop a set of comprehensive guiding principles of sustainable develop-ment so as to make them beneficial for governments and organizations which really want to maintain sustainable development for both present and future generations. This study, in addition, intends to conduct a survey to determine whether the complex of International Islamic School (IIS) under International Islamic University Malaysia (IIUM) fulfils these principles or not. This paper concludes that in Islam sustainable development requires balance between present and future life; and between worldly life and life hereafter. Keywords: Sustainable